An assessment of knowledge, attitude, and practice towards depression and video games among International Islamic University Malaysia students - Salleh, Anisa; Abdul Ghani, Radiah (Malaysian Journal of Medicine and Health Sciences, 2021)
This study aimed to identify the level of knowledge, attitude and practice of depression and video games. The as-sociated factors and the correlation between knowledge, attitude and practices about depression and video games among IIUM students were determined. A total of 140 IIUM students were drawn using convenience sampling. A self-developed questionnaire was validated before used to collect data. The response of participants was analysed using SPSS version 25.0. The level of knowledge, attitude and practice among respondents was evaluated using a descriptive frequency table, while independent sample t-test, ANOVA test, and Kruskal-Wallis test were used to find associating factors between depression and video games. Pearson correlation test was used to determine the correla-tion between knowledge, attitude, and practice. The results showed the level of knowledge and attitude are moder-ate while the level of practice is poor. Factors that have a significant association with knowledge are the adventure, sports, and puzzle games. Action-adventure and idle game, video game platform, and the amount of money spent on video games significantly affect attitude. For the association of factors with practice, idle game, preferred time-period for game session and amount of time spent per game session in a day showed significant association. There is also a significant correlation between knowledge and attitude. Overall, this study showed that increasing knowledge on the factors of excessive video gaming habits and the factors of video games that increase the risk for the development of depression can help tackle depression among youths in Malaysia.